2008
DOI: 10.1021/ol802417n
|View full text |Cite
|
Sign up to set email alerts
|

Stacked-Ring Aromaticity: An Orbital Model

Abstract: Visualization of induced current density using the ipsocentric CHF/CTOCD-DZ/6-31G** approach gives a direct demonstration of the literature proposal of reversal of [4n]annulene antiaromaticity on stacking cyclooctatetraene (COT) rings into a superphane. Through-space interactions lead to a closed-shell in which paratropicity of planar COT units is quenched, and layered diatropic currents arise from magnetic response of two pairs of frontier orbitals. A general orbital model rationalizes the differences in curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 14 publications
(34 reference statements)
6
69
0
Order By: Relevance
“…The excitation plot does not contain these extra contributions, and hence gives a more realistic picture of the current intensity. Comparing the j max values of the virtual excitations, it is tions to the p current (a feature also found in stacked-ring systems [20]) whereas the 4e 2 0 pair contributes proportionately only about half as much. This is compatible with the indication from orbital plots ( Figure S1, Supplementary Information) that this pair has significant iron d-orbital character.…”
Section: Compoundmentioning
confidence: 73%
See 2 more Smart Citations
“…The excitation plot does not contain these extra contributions, and hence gives a more realistic picture of the current intensity. Comparing the j max values of the virtual excitations, it is tions to the p current (a feature also found in stacked-ring systems [20]) whereas the 4e 2 0 pair contributes proportionately only about half as much. This is compatible with the indication from orbital plots ( Figure S1, Supplementary Information) that this pair has significant iron d-orbital character.…”
Section: Compoundmentioning
confidence: 73%
“…In 1 there appears to be a formal link with p-stacking in organic systems [20], in that two interacting diatropic rings retain their aromatic character when stacked face-to-face. Compound 2 displays 4-electron diatropic currents of the type consistently observed in ipsocentric studies of annulenes and other systems [8,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) can eliminate their antiaromaticity due to the resulting three-dimensional aromaticity, which results from mutual interactions between frontier orbitals of each π-system. This intriguing proposal was further supported by a theoretical study of Bean and Fowler9 on the ring current effect in antiaromatic cyclophanes with a very short interplanar distance between the two π-systems (∼2.2 Å). In such systems, intermolecular electronic delocalization should be significantly increased.…”
mentioning
confidence: 71%
“…From these results as well as the results for other ring size, the authors concluded that "stacking, along with triplet [42] and Möbius strategies [89,90], is the third way to render 4nπ electron system aromatic." CTOCD-DZ calculations [91] supported the conclusion, whereas an analysis based on energetic criteria using graph theory concluded that the stacking of antiaromatic ring does not bring about aromatic stabilization energy even though the original antiaromaticity is reduced [92]. …”
Section: Stacking Of Planar Cot Ringsmentioning
confidence: 91%